1987
DOI: 10.1037/0022-3514.53.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Audience response as a heuristic cue in persuasion.

Abstract: Previous research on the persuasive impact of an overheard audience has yielded conflicting results. In this study, we attempted to understand such audience effects within the framework of the heuristic model of persuasion. Subjects listened to an audiotaped persuasive message that conveyed arguments of either high or low quality and that was responded to by either an enthusiastic or an unenthusiastic overheard audience. In addition, subject involvement (high vs. low) was varied. Consistent with predictions, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
191
1
7

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(206 citation statements)
references
References 36 publications
7
191
1
7
Order By: Relevance
“…We further argue that in some cases, informational influence may take the form of mindlessly using the responses of others as heuristic cues to guide behavior (Cialdini, 1993). Consistent with this idea, past studies have indicated that people may apply the heuristic that ''consensus implies correctness'' and adopt the position of others when they perceive consensus between these other people towards that position (Axsom et al, 1987;Chaiken et al, 1996;Cialdini, 1993). From this reasoning, we therefore hypothesized that happy mood should engender greater use of the ''consensus implies correctness'' heuristic than negative mood and thus should produce stronger conformity effects than negative mood.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We further argue that in some cases, informational influence may take the form of mindlessly using the responses of others as heuristic cues to guide behavior (Cialdini, 1993). Consistent with this idea, past studies have indicated that people may apply the heuristic that ''consensus implies correctness'' and adopt the position of others when they perceive consensus between these other people towards that position (Axsom et al, 1987;Chaiken et al, 1996;Cialdini, 1993). From this reasoning, we therefore hypothesized that happy mood should engender greater use of the ''consensus implies correctness'' heuristic than negative mood and thus should produce stronger conformity effects than negative mood.…”
Section: Discussionmentioning
confidence: 60%
“…Although research on the systematic-heuristic model typically focuses on persuasion, the model has also been successfully applied to other domains such as person perception (Chaiken et al, 1989). Of relevance to our current interest in conformity, past studies have shown that people may apply the heuristic that ''consensus implies correctness'' in making sense of a situation (Axsom, Yates, & Chaiken, 1987). This suggests that in a conformity context, people may be more likely to infer that a certain position is correct to the extent that other people unanimously agree on that position.…”
mentioning
confidence: 93%
“…Since the strength of consensus decision making varies between individualists and collectivists, 113,114 this will also influence the decision about brand association based on selfcongruity and hence brand preference.…”
Section: Influence Of Consensus Decision On Self-conceptmentioning
confidence: 99%
“…Given research on the judgmental impact of consensus information (e.g., Axsom, Yates, & Chaiken, 1987;Maheswaran & Chaiken, 1991), we added a measure to assess consensus opinion beliefs. We expected that all participants may infer consensus opinion and subsequently base their attitudes at least in part on a "consensus opinions are correct" heuristic.…”
Section: Studymentioning
confidence: 99%